2015
DOI: 10.1016/j.stem.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Naive Induced Pluripotent Stem Cells from Rhesus Monkey Fibroblasts

Abstract: A reader has pointed out that there are duplications of some of the lanes presented in Figure 2B of our originally published manuscript. Upon examination of the affected lanes and the original data, we discovered that there is indeed duplication caused by inadvertent inclusion of erroneous image files during our organization of the published data.In Figure 2B of the original manuscript, the lanes of SALL4 presented are duplications of the lanes of CRIPTO, and the lanes of DNMT3B presented are duplications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Human or non-human primate PSCs with some features of naïve pluripotency have been derived by the conversion of conventional hESCs or induced PSCs (iPSCs) in vitro, through reprogramming of somatic cells to a pluripotent state or by direct derivation from the embryo (Tables 2 and 3) (Buecker et al, 2010;Chan et al, 2013;Fang et al, 2014;Gafni et al, 2013;Hanna et al, 2010;Li et al, 2009;Takashima et al, 2014;Theunissen et al, 2014;Valamehr et al, 2014;Ware et al, 2014. Early studies used exogenous transgenes to trigger the conversion from primed to naïve pluripotency and, in some cases, to stabilise and maintain the naïve state.…”
Section: Towards Human Naïve Pscs?mentioning
confidence: 99%
“…Human or non-human primate PSCs with some features of naïve pluripotency have been derived by the conversion of conventional hESCs or induced PSCs (iPSCs) in vitro, through reprogramming of somatic cells to a pluripotent state or by direct derivation from the embryo (Tables 2 and 3) (Buecker et al, 2010;Chan et al, 2013;Fang et al, 2014;Gafni et al, 2013;Hanna et al, 2010;Li et al, 2009;Takashima et al, 2014;Theunissen et al, 2014;Valamehr et al, 2014;Ware et al, 2014. Early studies used exogenous transgenes to trigger the conversion from primed to naïve pluripotency and, in some cases, to stabilise and maintain the naïve state.…”
Section: Towards Human Naïve Pscs?mentioning
confidence: 99%
“…Recently, several studies have reported the generation of naive-like human pluripotent stem cells (PSCs) and monkey induced PSCs (iPSCs) by using different combinations of pharmacological agents and cytokines (Hackett and Surani, 2014). Two of these studies reported that growth of PSCs in a media formulation termed NHSM or modified NHSM could yield naive-like human or monkey PSCs with the ability to contribute to interspecies chimeric embryos after their injection into mouse E2.5 morulae (Fang et al, 2014;Gafni et al, 2013). However, it is not known whether primate ESCs have the capacity to generate monkey chimeras.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, it was shown recently that deriving and maintaining naïve human and monkey PSCs require bFGF (Fang et al, 2014;Gafni et al, 2013;Theunissen et al, 2014), which for a long time has been considered as a marker for primed PSCs on the basis of the knowledge gained from mouse and rats. Here, we have demonstrated that bFGF is also indispensable for the derivation as well as the maintenance of rbESCs.…”
Section: Discussionmentioning
confidence: 99%